IMPLEMENTATION OF THE ZONING SYSTEM POLICY IN NEW HIGH SCHOOL ADMISSIONS IN THE CITY OF SUKABUMI - Yusran Reirenza; M. Rijal Amirulloh; Dine Meigawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Starting in 2017, the Indonesian education world implemented a zoning policy in the acceptance of new students (PPDB). The zoning system is a system for accepting new students by applying zones or distances between the residence of prospective students and the school as the main point in accepting new students. In the implementation of the Peraturan Gubernur Jawa Barat Nomor 29 Tahun 2021 on Technical Guidelines for Accepting New Students in Senior High Schools, Vocational High Schools, and Special Schools, there are still many pros and cons in its implementation in schools. The purpose of this study is to find out the implementation of the zoning policy in the acceptance of new students in senior high schools in the city of Sukabumi. The unit of analysis that will be studied is the Branch of Regional Office V of Sukabumi City. Data collection is done using observation, in-depth interviews, and documentation. Data analysis is done qualitatively. The results show that the implementation of the PPDB policy with the zoning system according to the communication dimension in its implementation can be said to be good. Although there are still obstacles and constraints in the form of information misunderstandings in the field, overall it is optimal.